(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Philosophical analyzes of society and its development are presented in the article, in which deep scientific thoughts of philosophers are elaborated and analyzed. In particular, an attempt has been made to connect their ideas with the present-day trends, focusing on the details of modern-day traditions.